Incidência de HTLV-1/2 em candidatos à doação de sangue do Amazonas : um estudo observacional comparando diferentes métodos de diagnóstico - Santos, Felipe Araújo dos (2023)
Human T-cell lymphotropic virus is a retrovirus, which was discovered in 1980 and specifically isolated from a patient with cutaneous T-cell lymphoma. Over the years, HTLV types have been identified, totaling four types (HTLV-1, HTLV-2, HTLV-3 and HTLV-4). Although most of those infected with one or more types are asymptomatic carriers, 2 to 5% of this infected population may present with chronic encephalomyelopathy and HTLV-1- associated myelopathy/tropical spastic paraparesis (HAM/TSP). The methodologies for virus diagnosis are: chemiluminescence (CLIA); enzyme-linked immunosorbent assay (ELISA), used in the qualitative phase or screening for the virus, this phase is responsible only for its detection in the sample of the infected. The confirmation or distinction of the virus is performed by: western blot (WB) or polymerase chain reaction (PCR), in the confirmatory phase. The tests have negative particularities that decrease their diagnostic capacity being used separately or increase their high costs when used together. Therefore, the present study evaluated the incidence of HTLV-1/2 in blood donors treated at the HEMOAM foundation from 2018 to 2022, using commercial and conventional methodologies for diagnosis as well as new FC-Duplex and FC-Simplex HTLV-1/2 IgG1 assays, in addition to the evaluation of these methodologies, updating sociodemographic data of blood donor infection in Amazonas. A total of 409 donors were found to be unfit for blood donation by CLIA during the survey period. Only 151 individuals of the total found accepted through a free and informed consent form (ICF) to participate in the project. We conclude with the evaluations carried out the maintenance of the low prevalence (0.15%) of the virus among the studied group. The good performances of the WB and CLIA methodologies in their due stages of use, as well as the promise of using the FC-Simplex and FC-Dlupex HTLV-1/2 IgG1 assays as a diagnostic method for the virus